LEXICAL-SEMANTIC AND COGNITIVE ANALYSIS OF UNITS WITH THE “WATER” COMPONENT IN THE TOPONYMIC SYSTEM - Muminova, Masuma Golibovna (SCIENCE and SOCIETY, 2026)
This article is devoted to the study of the lexical-semantic and cognitive characteristics of place names formed with the component “suv/water” within the toponymic system. The research provides a scientific analysis of this component's role in onomastic units, its functional tasks in nomination, and its semantic scope. The author classifies toponymic models resulting from the combination of the lexeme “suv” with semantic categories such as color, quality, movement, and volume. Additionally, the article highlights the interaction between human perception of geographical objects and linguistic nomination patterns in the formation of hydronyms. The findings of the study contribute to determining the semantic derivation of toponyms and their conceptual significance within the system of regional names.
Keywords: toponymy; hydronym; “suv” component; semantic feature; onomastics; nomination; lexical-semantic analysis; linguocognitology; place names